Cytochrome Oxidase Repair during Treatment of Copper Deficiency: Relation to Mitochondrial Turnover - Dallman, Peter R. (1967)
The repair of cytochrome oxidase depletion during the treatment of copper deficiency was studied in the rat. The purpose of this study was to distinguish the role of new cell production from the possibly more specific role of mitochondrial turnover in determining the rate of this repair. In rats on a copper-deficient regimen until 2.5-3 months of age, activities of cytochrome oxidase expressed as per cent of control were as follows: skeletal muscle (quadratus lumborum), 18%; heart, 27%; liver, 34%; and intestinal mucosa, 34%. After 2-3 days of dietary supplementation with cupric acetate, repair of decreased cytochrome oxidase activity in intestinal mucosa is complete. Histochemical studies indicated that this repair starts in the newly differentiating cells at the base of the villus and then progresses toward the tip of the villus at a rate approximating the normal rate of migration of the mucosal cells. In liver and skeletal muscle, cytochrome oxidase activity returned to control values after 10-15 days of treatment with cupric acetate. In heart muscle, control values were approached more slowly as indicated both by activity of the enzyme and by mitochondrial difference spectra which reflect enzyme concentration. Although cytochrome oxidase repair in the intestine appeared to be limited by the rate of production of new mucosal cells, the rate of repair in liver and skeletal muscle was several times too rapid to be accounted for by known rates of new cell production. Incorporation of tritiated thymidine into DNA in these tissues in both the deficiency state and during repair indicated no major differences in new cell production compared to that of control animals. However, the time required for cytochrome oxidase repair in liver was similar to the turnover reported for other mitochondrial constituents in this tissue. The rate of cytochrome oxidase repair may therefore be more directly determined by the rate of synthesis of new mitochondrial material than by the rate of production of new cells.